2016
DOI: 10.1097/acm.0000000000001007
|View full text |Cite
|
Sign up to set email alerts
|

Creating the Exceptional Patient Experience in One Academic Health System

Abstract: Whether patient satisfaction scores can act as a catalyst for improving health care is highly debated. Some argue that pursuing patient satisfaction is overemphasized and potentially at odds with providing good care because it leads providers to overtest and overtreat patients and to bend to unreasonable patient demands, all to improve their ratings. Others cite studies showing that high patient satisfaction scores correlate with improved health outcomes. Ideally, assessing patient satisfaction metrics will en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 17 publications
0
43
0
Order By: Relevance
“…Effective communication and empathetic behaviors are crucial aspects of patient care. Other research has revealed that physicians who are empathetic and include the patients in the decision-making process of their treatment are highly evaluated 1,19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective communication and empathetic behaviors are crucial aspects of patient care. Other research has revealed that physicians who are empathetic and include the patients in the decision-making process of their treatment are highly evaluated 1,19…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefits of improving patient satisfaction are staggering. Patient satisfaction is a useful measure of patient care and can be used to improve a practice’s performance and profitability 1. For example, in 2008, a health system consisting of inpatient care, primary care, and pediatrics adopted patient satisfaction surveys.…”
Section: Introductionmentioning
confidence: 99%
“…[4,26] Healthcare coordination Satisfaction surveys among patients Use of questionnaires and/or interviews between patients and clinicians in order to collect and measure patient's satisfaction regarding some specific aspects of healthcare/services provided by the hospital, based on appropriated scores of satisfaction and quality of life. [17,27,28] Participation to weekly multidisciplinary sessions of analysis of clinical cases [7,25,29,30] Optimization of patient flows Patient flow: process of quickly and efficiently attending to patients through the different stages of care, from the time they walk into the medical facility to the time of discharge. [3,31,32] (Continued) Poles of care: Grouping some specific medical departments within the spatial architecture of the medical facility in order to improve the management of some specific diseases/groups of diseases that require these specific services.…”
Section: Methodsmentioning
confidence: 99%
“…Medicare Hospital Compare has become a powerful tool for patients as they chose the provider best suited for them, in terms of cost, outcomes, and physician characteristics. Other hospitals have gone farther and have made all of their provider's experience data, including HCAHPS scores and comments, available online [34,35]. Such transparency will only continue to grow as it provides an impetus for hospitals and providers to improve outcomes, experience, and reputation.…”
Section: Embracing Transparency Consumerism and Technologymentioning
confidence: 99%
“…Some have suggested that focusing on patient experience is dangerous and that it leads to increased testing and overtreatment, which results in negative health outcomes [16][17][18]. One of the more frequently cited studies looked at patient experience in conjunction with healthcare utilization and mortality [18].…”
Section: Clinical Outcomesmentioning
confidence: 99%